DEKONSTRUKSI MATERIALISME : (ANALISIS ISI MEDIA GUBERNUR JABAR DALAM MENGEMBALIKAN NILAI-NILAI KEBANGSAAN) - Taufik, Cevi M (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
Materialism has taken root in the souls of modern agents. The irony is that in difficult living conditions, they are reluctant to admit that they are difficult. Hedonistic and have a life view that is contrary to the spirit and soul of the nation. For some people who apply this understanding, materialism is the main view. So, whatever they do must end in material. Without material, every activity will not run. Likewise, their concern for others has diminished. Sadly, this reality has been going on for decades and has not been a concern for previous leaders. So in this context, the Governor of West Java, Dedi Mulyadi, appeared by deconstructing the understanding that had long infiltrated the national ideology. Based on these conditions, the study aims to determine Dedi Mulyadi's steps in re-establishing local wisdom values ​​as a form of deconstruction of the materialist understanding that has infected the nation's citizens. Using a qualitative approach with a type of content analysis method, this study emphasizes data sourced from Dedi Mulyadi's content that is widely spread on online networks. The results show that Dedi Mulyadi's concrete steps are able to make people aware of the true nature and identity of this nation.